Digital Resistance and Representation: Media Narratives of Marginalized Groups in a Global Context - Jariah, Ainun (Communica : Journal of Communication, 2025)
Media representations of marginalized communities significantly influence public perceptions and social inclusion. This narrative review aims to analyze how traditional and digital media construct narratives about marginalized groups, oscillating between reinforcing stereotypes and fostering empowerment. A comprehensive literature search was conducted using Scopus, Google Scholar, and EBSCOhost, focusing on studies employing keywords such as "media representation," "marginalized communities," "stereotypes," and "empowerment." Inclusion criteria emphasized peer-reviewed articles examining media portrayals of socially excluded populations. Findings reveal persistent stereotypes across media, with portrayals often simplifying and stigmatizing LGBTQIA+ individuals, people with disabilities, and ethnic minorities. Such portrayals contribute to psychological distress and reinforce systemic exclusion. However, emerging narratives facilitated by social media platforms offer spaces for resistance, identity articulation, and inclusive storytelling. Examples from participatory cinema, community radio, and TikTok campaigns show how marginalized voices challenge hegemonic discourses and reshape public understanding. Discussion highlights the systemic nature of media bias and the role of inclusive policies in promoting equity. Disparities between media practices in developed and developing countries are evident, pointing to the need for culturally sensitive reforms. This review calls for future research into digital media's transformative potential and recommends policy frameworks that integrate marginalized voices in content creation.